THE DETERMINANTS OF CUSTOMER LOYALTY IN SHARIA BANK IN JAMBI WITH ISLAMIC APPROACH - Lucky Enggrani Fitri; Paulina Lubis; Ary Dean Amri (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
This study aimed to determine the direct effect between customer perceived value (CPV), trust towards satisfaction on customer of sharia banks in Jambi province. The development of Sharia banking in Jambi is quite slow compared to other provinces in Sumatra Island. This research was conducted in Jambi Province. The design of this study used a quantitative method with a survey approach to obtain primary data, namely by distributing questionnaires to 140 customers in six Sharia commercial banks in Jambi province by using purposive sampling method in determining the sample. Determination of the minimum sample size in this study refers to the statement of Hair et al. Then the quantitative data was processed using Structural Equation Model (SEM) with SmartPLS 3 software. The findings of this study found that an exogenous latent variable Customer Perceived Value affects customer trust and satisfaction. This research was expected to make practical contributions to the management of Sharia banks and related parties as information to determine the marketing strategy of Sharia bank products in Jambi province, in effort to increase customer satisfaction of sharia banks in Jambi province.